Anti-Ri-associated paraneoplastic neurological syndrome: Initial symptom of breast cancer with HER2 overexpression and treatment by dual HER2 blockade. (September 2019) - Olmez, Omer Fatih; Kinikoglu, Oguzcan; Yilmaz, Nesrin Helvacı; Bilici, Ahmet; Cubukcu, Erdem; Seker, Mehmet; Cakir, Tansel; Yildiz, Ozcan; Hamdard, Jamshid
Paraneoplastic neurological syndrome is associated with anti-Ri antibodies, which are typically present with opsoclonus–myoclonus–ataxia. Human epidermal growth factor receptor 2 (HER2) overexpression is present in 15%–25% of breast cancer and is associated with poor prognosis. There are a few reports of paraneoplastic neurological syndrome associated with HER2-positive breast cancer in the literature, of which most are anti-Yo-associated paraneoplastic neurological syndrome. We present herein the case of a female patient with HER2-positive breast cancer who had atypical anti-Ri antibody associated with opsoclonus–myoclonus paraneoplastic neurological syndrome. Following the diagnosis of paraneoplastic syndrome, chemotherapy with dual HER2 blockade and immunomodulating treatment including intravenous immunoglobulin and oral prednisolone were administered. Although the patient was negative for serum anti-Ri antibodies, there was partial clinical improvement and her neurological deficit persisted. To our knowledge, this is the first case report of female patient with HER2-positive breast cancer who had atypical anti-Ri antibody associated with opsoclonus–myoclonus paraneoplastic neurological syndrome and treated with dual HER2 blockade.